رأس المال الفكري كأداة لمواجهة تداعيات إتفاقية حقوق الملكية الفكرية على الدول النامية - شرف الدين أمين, أ/ بن عواق (Sciences humaines, 2009)
جاءت العولمة الاقتصادية كنتيجة لذلك التطور الهائل في وسائل الاتصال والمعلومات، صاحب ظهورها تغيير في المعطيات العامة التي تحكم النشاط الاقتصادي حيث اتجهت الكفة لصالح الجوانب المرتبطة بالمعرفة والأصول الفكرية وأصبحت قواها تدعم وتعزز مبادئ إتفاقية حقوق الملكية الفكرية وفقا لمعايير موحدة.       على هذا الأساس تسعى هذه الدراسة للتطرق الى مدخل رأس المال الفكري باعتباره وسيلة فعالة واحد الحلول المتاحة للدول عموماً والدول النامية على وجه الخصوص لما له من امكانيات ومؤهلات متميزة من أجل مواجهة تداعيات إتفاقية حقوق الملكية الفكرية وتحقيق الاندماج والتكيف الجيدين مع المعطيات الجديدة التي تفرضها هذه الاتفاقية    The economic globalization emerged thanks to the massive development means of communication and information.  This led to a change in the general data that manage the economic activity, where the balance turned in favor to sides that are related with knowledge and intangible assets Its efforts became supporting and promoting the principals of rights intellectual property agreement in accordance with specific criteria.        On this bases, this study is seeking to address the way to the intellectual capital as an effective mean and one of the available solutions to countries in general and developing countries in particular, for what it has of capacities and unique qualifications for facing the fallouts of the right  intellectual property agreement and achieve the well  integration and adaptation with new data that is imposed by this agreement.